Linalool attenuated ischemic injury in PC12 cells through inhibition of caspase‐3 and caspase‐9 during apoptosis. Issue 1 (20th September 2022) - Hosseini, Azar; Pourheidar, Elham; Rajabian, Arezoo; Asadpour, Elham; Hosseinzadeh, Hossein; Sadeghnia, Hamid Reza
Abstract: Numerous studies have indicated the pharmacological properties of linalool, a volatile terpene alcohol found in many flowers and spice plants, including anti‐nociceptive, anti‐inflammatory, and neuroprotective activities. The aim of this study was to explore the mechanisms of neuroprotection provided by (±) linalool and its enantiomer, ( R) ‐(−) linalool against oxygen, and glucose deprivation/reoxygenation (OGD/R) in PC12 cells. PC12 cells were treated with (±) linalool and ( R) ‐(−) linalool before exposure to OGD/R condition. Cell viability, reactive oxygen species (ROS) production, malondialdehyde (MDA) level, DNA damage, and the levels of proteins related to apoptosis were evaluated using MTT, comet assay, and western blot analysis, respectively. IC50 values for the PC12 cells incubated with (±) linalool and (R) ‐(−) linalool were 2700 and 2600 μM after 14 h, as well as 5440 and 3040 μM after 18 h, respectively. Survival of the ischemic cells pre‐incubated with (±) linalool and ( R) ‐(−) linalool (100 μM of both) increased compared to the cells subjected to the OGD/R alone ( p  < .001). ROS and MDA formation were also decreased following incubation with (±) linalool and (R) ‐(−) linalool compared to the OGD/R group ( p  < .01). In the same way, pre‐treatment with (±) linalool and (R) ‐(−) linalool significantly reduced OGD/R‐induced DNA injury compared to that seen in OGD/R group ( p  < .001). (±) Linalool and (R) ‐(−) linalool also restored Bax/Bcl‐2 ratio and cleaved caspase‐3 and caspase‐9 ( p  < .001, p  < .01) following ischemic injury. The neuroprotective effect of linalool against ischemic insult might be mediated by alleviation of oxidative stress and apoptosis. Abstract : This study indicated, for the first time, that (±) linalool and its enantiomer, (R)‐(‐) linalool protected PC12 cells against injury induced by oxygen and glucose deprivation/reoxygenation (OGD/R) via the mitigation of oxidative stress and the downregulation of Bax/Bcl‐2, caspase‐3 and caspase‐9, resulting in decreased apoptotic cell death.